Polysomnography Following Traumatic Brain Injury: A Systematic Review and Meta-Analysis. (1st June 2022) - Bray, M.; Krieg, A.; Esagoff, A.; Bryant, B.; Salas, R.; Rao, V.; Peters, M.
Abstract : Introduction: Sleep disturbances are common following traumatic brain injury (TBI) worsening morbidity and other neuropsychiatric symptoms. Post-TBI alterations in sleep architecture require further study. Objectives: (1) To evaluate polysomnographic measures of sleep architecture in participants with history of TBI compared to controls and as meta-analyses of pooled means. (2) To evaluate effects of timing and severity of TBI on polysomnographic outcomes. Methods: PRISMA compliant systematic review was conducted of MEDLINE, PsycINFO, EMBASE and Scopus. Inclusion criteria: 1) reporting polysomnography in the context of TBI and 2) operationalizing TBI using clear/formalized criteria. Data were pooled in random-effects meta-analyses with outcomes expressed as mean differences (MD). Results: In participants with TBI, sleep was comprised of 19.39% REM sleep, 8.13% N1, 51.18% N2, and 17.53% N3, as determined by meta-analyses of single means. Total sleep time was reduced in chronic (>6 months) TBI compared to acute-intermediate TBI (<6 months) ( p =0.01). Compared to controls, participants with TBI differed with increased N1 sleep (MD=0.64%; 95%CI=0.02, 1.25; p =0.04), reduced sleep efficiency (MD=-1.65%; 95%CI=-3.18, -0.12; p =0.03), and reduced sleep latency on the multiple sleep latency test (MD=-5.90mins; 95%CI=-10.09, -1.72; p <0.01). On sub-group analyses, participants with mild TBI differed from controls with reduced total sleep time (MD=-29.22mins, 95%CI=-54.16, -4.27; p =0.02). Similarly, participants with acute-intermediate TBI exhibited increased sleep latency compared to controls (MD=8.96mins; 95%CI=4.07, 13.85; p <0.01) and differed significantly from participants with chronic TBI ( X 2 (1, N=608)=6.54; p =0.01). Conclusions: Sleep architecture is altered following TBI with potential implications regarding functional outcomes and recovery. These alterations appear to differ based on severity of injury and time since injury. Disclosure: No significant relationships.